The Rise of Queryless Analytics: Transforming Enterprise Data Interaction through AI - Siddhartha Parimi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The emergence of queryless data analytics, powered by advanced artificial intelligence, marks a transformative shift in how organizations interact with their data assets. This article examines the evolution from traditional SQL-based querying to natural language processing-driven analytics, focusing on the architectural frameworks and enterprise implementations of leading solutions like Databricks AI Assistant, Snowflake Cortex, and Tableau AI. An article on current industry adoption patterns and technical capabilities, explores how these AI-powered systems are democratizing data access while maintaining robust security and governance frameworks. This article demonstrates that conversational interfaces for data analytics are not merely simplifying query processes but are fundamentally restructuring data team dynamics and workflows across enterprises. It also suggests that this paradigm shift represents a crucial step toward true data democratization, though challenges in areas such as context understanding and complex query optimization remain. It concludes by examining the broader implications for enterprise data strategy and the future of business intelligence tooling.